Existence of global attractors for two-dimensional Newton–Boussinesq equation. (July 2017) - Song, Xue-li; Wu, Jian-hua
Abstract: In this paper, we study global attractors of two-dimensional Newton–Boussinesq equation. We obtain the existence of H 0 1 ( Ω ) × H 0 1 ( Ω ) -global attractors and H 2 ( Ω ) × H 2 ( Ω ) -global attractors in two-dimensional bounded domains. Meanwhile, we get the existence of H 0 1 ( Ω ) × H 0 1 ( Ω ) -global attractors in two-dimensional channels.